Identification of bacteria in Rhizophora mucronata leaf litter and sediment - YULMA YULMA; ASIHING KUSTANTI; SOEMARNO SOEMARNO; MOHAMMAD MAHMUDI; BURHANUDDIN IHSAN (Society for Indonesian Biodiversity, 2025)
Abstract. Yulma, Kustanti A, Soemarno, Mahmudi M, Ihsan B. 2025. Identification of bacteria in Rhizophora mucronata leaf litter and sediment. Biodiversitas 26: 3054-3060. The mangrove ecosystem is an area that has high productivity, with litter production that contributes to increasing nutrients. This study aimed to determine the bacterial community in mangrove vegetation, especially in sediment and decomposed Rhizophora mucronata leaf litter. This study was conducted in the Mangrove and Crab Conservation Area. R. mucronata leaf litter was collected with a 2 × 2 m container. Furthermore, the leaf litter was dried at 105°C until its weight was constant. The decomposition rate and bacterial identification were measured at intervals of 14, 28, 42 and 56 days. Meanwhile, sediment was taken at different depths, namely 10, 20, and 30 cm, and as much as 250 g for each depth using a biopore drill. Identification of bacteria in litter and sediment was carried out with three tests, namely: Gram staining test (Gram-negative, Gram-positive and bacterial forms), primary test (3% KOH, 3% H2O2 and Oxidase) and further test (O/f, Glucose and motility). The results showed that the bacterial community that plays a role in decomposing organic matter and accelerating the rate of decomposition in R. mucronata leaf litter is diverse with different characteristics, including Bacillus sp., Aeromonas sp., Pseudomonas sp., Listeria sp., Actinobacillus sp., Micrococcus sp., and Acinetobacter sp. At the same time, the bacterial community found in the sediment includes Pseudomonas sp., Aeromonas sp., Micrococcus sp., Bacillus sp., Flavobacterium sp., Enterobacteria sp., and Listeria sp. The most dominant bacteria found is Bacillus sp. because one of the endophytic bacteria found in plant tissue can increase plant growth through mechanisms such as biological nitrogen fixation, phosphate and potassium solubilization.